2011
DOI: 10.1016/j.envint.2010.12.007
|View full text |Cite
|
Sign up to set email alerts
|

A first evaluation of the usefulness of feathers of nestling predatory birds for non-destructive biomonitoring of persistent organic pollutants

Abstract: In previous studies, feathers of adult predatory birds have been evaluated as valid non-destructive biomonitor matrices for persistent organic pollutants (POPs). In this study, we assessed for the first time the usefulness of nestling raptor feathers for non-destructive biomonitoring of POPs. For this purpose, we collected body feathers and blood of nestlings from three avian top predators from northern Norway: northern goshawks (Accipiter gentilis), white-tailed eagles (Haliaeetus albicilla) and golden eagles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 45 publications
3
35
2
Order By: Relevance
“…The OC exposure in raptors from Argentina found in this study were much higher than those found in feathers of raptors from northern Norway and South-west Iran (Eulaers et al, 2011;Behrooz et al, 2009a), and feathers of seabirds from Spain (Espín et al, 2012) and mongolian plover (Charadrius mongolus) from South India (Tanabe et al, 1998). Several factors may have led to the high OC concentrations found in our study.…”
Section: Oc Concentrations In Feathers and Profilecontrasting
confidence: 54%
“…The OC exposure in raptors from Argentina found in this study were much higher than those found in feathers of raptors from northern Norway and South-west Iran (Eulaers et al, 2011;Behrooz et al, 2009a), and feathers of seabirds from Spain (Espín et al, 2012) and mongolian plover (Charadrius mongolus) from South India (Tanabe et al, 1998). Several factors may have led to the high OC concentrations found in our study.…”
Section: Oc Concentrations In Feathers and Profilecontrasting
confidence: 54%
“…Besides internal assimilation through diet during feather growth when the feather is connected to the bloodstream and metals are integrated in the keratin structure (Tsipoura et al, 2008), metals may be externally deposited on the feathers of exposed birds from the environment and/or through preening (Dauwe et al, 2003;Cardiel et al, 2011;Jaspers et al, 2004). Monitoring of pollutant concentrations using bird feathers as a matrix, has proven to be a useful tool for assessing environmental quality of aquatic and terrestrial habitats (Eulaers et al, 2011;Garcia-Fernandez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Birds have been successfully used as sentinel species to monitor the levels and effects of POPs in the environment because they are widespread, sensitive to environmental changes, and often high on the food chain (Dauwe et al, 2006;Van den Steen et al, 2010a,2010bCuster et al, 2012;Sun et al, 2012;Eng et al, 2014). Predatory birds have been widely used as biomonitoring species for POPs (Chen et al, 2009b;Chen and Hale, 2010;Eulaers et al, 2011;Gómez-Ramírez et al, 2014), but most of these birds are less suitable to reflect the local contamination status because they are migratory and live in an extended area with low population densities (Dauwe et al, 2006(Dauwe et al, , 2009. Thus, resident passerine bird species have been successfully used as biomonitoring tools to determine POPs contamination (Dauwe et al, 2009;Van den Steen et al, 2010b;Eens et al, 2013;Morrissey et al, 2013;Eng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%